2014
DOI: 10.3354/meps11010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prey concentration on ingestion rates of European sardine Sardina pilchardus larvae in the laboratory

Abstract: The quantification of prey requirements for larval fish is essential to understand how environmental factors act to restrict suitable habitats and recruitment success in marine fish. The effect of prey concentration on ingestion rates of the European sardine Sardina pilchardus was estimated for larvae through 50 d post-hatch (dph) under controlled laboratory conditions at 15°C. Prey were nauplii and copepodites of the calanoid copepod Acartia grani, which were provided to larvae at 3 concentrations (0.5, 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Finally, the carbon consumption rate may be divided by the total number of larvae, which gives 1.2 µg C larva −1 h −1 . The latter result is within the same order of magnitude compared to previously published figures by Caldeira et al [90], who reported carbon intake rates for sardine species Sardina pilchardus in European waters between 4.5 and 7 µg C larva −1 h −1 . The relatively lower carbon consumption rate observed here for Sardinella aurita may be due to the fact that (1) the European Sardina pilchardus is likely to present anatomical and physiological differences, as well as living in different environmental conditions, compared with the species Sardinella aurita studied here in Ivorian waters; and (2) our calculation is based on total Sardinella catch, and this value is likely to underestimate the total number of Sardinella individuals present in the study area (i.e., not all Sardinella may have been caught).…”
Section: Influence Of Biophysical Conditions On the Recruitment Of Sasupporting
confidence: 90%
“…Finally, the carbon consumption rate may be divided by the total number of larvae, which gives 1.2 µg C larva −1 h −1 . The latter result is within the same order of magnitude compared to previously published figures by Caldeira et al [90], who reported carbon intake rates for sardine species Sardina pilchardus in European waters between 4.5 and 7 µg C larva −1 h −1 . The relatively lower carbon consumption rate observed here for Sardinella aurita may be due to the fact that (1) the European Sardina pilchardus is likely to present anatomical and physiological differences, as well as living in different environmental conditions, compared with the species Sardinella aurita studied here in Ivorian waters; and (2) our calculation is based on total Sardinella catch, and this value is likely to underestimate the total number of Sardinella individuals present in the study area (i.e., not all Sardinella may have been caught).…”
Section: Influence Of Biophysical Conditions On the Recruitment Of Sasupporting
confidence: 90%
“…Presently, there are already very realistic hydrodynamical models developed for the region (e.g., Tanner et al 2017;Lamas et al 2017) but the coupling with NPDZ models is still in its infancy in this region (e.g., Reboreda et al 2014). Results from several laboratory experiments about sardine biological traits are now available regarding larvae feeding (Caldeira et al 2014, growth (Moyano et al 2014;, mortality (Garrido et al 2015a, predation (Pereira et al 2014) and…”
Section: Final Remarksmentioning
confidence: 99%
“…The time spent swimming and the foraging behaviour of sardine larvae increased with age/size. The increase in the frequency of prey capture with age/size is a consequence of larger larvae swimming faster (Silva et al 2014) and being able to capture prey within a wider size range (Caldeira et al 2014). By being able to select larger prey, larger larvae maximize the net rate of energy gain, because, all other things being equal, larger prey yield more energy per unit effort.…”
Section: Discussionmentioning
confidence: 99%
“…Both K and C were expressed in carbon units (µg C) by using available conversions of larvae length to carbon content and prey mean length of prey (Paracartia grani) to carbon content (Caldeira et al 2014). Statistical ana lyses were performed using Matlab 8.1 (R2013a) from Mathworks (mortality data) and the open source software R version 2.9.2 of R Development Core Team (growth and behavioural data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation